In silico Analysis and Characterization of a Putative Aspartic Proteinase Inhibitor, IA3 from Lachancea kluyveri - Jankangram, Wichuda; Chooluck, Sunthorn (Trends in Sciences, 2023)
Aspartic proteinases play important role in various physiological and biological processes. Understanding catalytic mechanisms of these enzymes could lead to crucial medical and biological applications. Two types of aspartic proteinase inhibitors have been identified i.e. small molecule inhibitor and naturally occurring peptides. Most of aspartic proteinases are highly susceptible to inhibition by a series of small, non-proteinaceous natural products; pepstatin. However, only limited number of naturally-occurring polypeptide inhibitors of aspartic proteinases has so far been discovered. One among these inhibitors is Saccharomyces cerevisiae IA3. The S. cerevisiae Proteinase A (ScPrA) is solely and potently inhibited by this small polypeptide at sub-nanomolar level. It was proven that, not only IA3 has no detectable effect against a wide range of aspartic proteinases, but it was also shown to be cleaved as a substrate of these non-target enzymes. Bioinformatics analysis of the IA3 structure has been undertaken in this study. Database searching for sequence homology from available fungal genome data bank using the Basic Local Alignment Search Tool (BLAST) revealed that 4 structurally related, IA3-like proteins have successfully been identified. The amino acid sequence of IA3-like proteins from Lachancea kluyveri share highest degree of similarity toward wild-type IA3. The Lk-IA3-like gene was synthesized using a PCR-based gene synthesis method. Protein expression in E. coli, protein purification and characterization of Lk-IA3-like by enzyme kinetic assays were performed. The results indicated that Lk-IA3-like protein inhibits ScPrA at the Ki value of 190 ± 0.11 nM and possesses no inhibitory effect toward AfPrA (Aspergillus fumigatus proteinase A) or HuCatD (Human cathepsin D). HIGHLIGHTS Aspartic proteinases enzyme family is crucially involved in various physiological and biological processes including in the pathogenesis of numerous diseases which make them a possible target for drug design Inhibitors of aspartic proteinases are not only applied for human disease treatment but also extended to plant and other economically important animals Aspartic proteinase from cerevisiae (Proteinase A) is solely and potently inhibited by a small peptideinhibitor, IA3 Bioinformatics analysis of the naturally occurring aspartic proteinases inhibitor, IA3 structure has been undertaken in this research and putative IA3-like proteins have successfully been identified IA3-like proteins from Lachancea kluyveri were produced in coli and enzyme inhibition assays revealed that Lk-IA3-like protein inhibits ScPrA at the Ki value of 190 ± 0.11 nM GRAPHICAL ABSTRACT